Development of PPS' document management system towards integration in producing an efficient performance / Nor Azlin Rosli - Rosli, Nor Azlin (2004)
This report was focused on Development on PPS' Document Management System towards Integration in Producing an Efficient Performance. The purpose of this project was to make integration between the eDMS (Enterprise Document Management System) and other application that existed especially with the e-mail application used and to make an enhancement on the eDMS interface to have more functionality. This project was basically developed for Centre for Strategic Planning, one of the departments in MARA University of Technology (UITM), Shah Alam. The eDMS is actually the Enterprise Document Management System which is used to manage all the important document, data and information that have been handled by this department. The Intranet is an ever changing medium that has been used to get connected with each other. A hybrid methodology taken from Knowledge Management Methodology and the EDMS Methodology will be mainly used in this project development which it consists of six phase that is planning, analysis, procurement, installation and testing, followed by development, implementation and finally the post implementation review for the project development. In order to meet the aim stated, a study had been made which started with problem investigation and ended with the development of the system. The Lotus Software such as Lotus Domino.Doc, Lotus Notes, and Lotus Domino Designer were used in the development of the eDMS.